2019
DOI: 10.1016/j.rboe.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do ácido zoledrônico e do alendronato no edema ósseo e dor na osteonecrose espontânea do joelho: Um novo paradigma no manejo

Abstract: Objective The aim of the present study was to determine the effect of combined zoledronic acid and alendronate therapy on bone edema and knee pain in cases of spontaneous osteonecrosis of the knee. We report our experience with this treatment. Methods A retrospective case series of 11 patients with spontaneous osteonecrosis of the knee confirmed by magnetic resonance image (MRI). The patients were treated with a single dose of 5 mg of intravenous zoledronic acid combined with 35 mg twice a week of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(77 reference statements)
2
8
0
1
Order By: Relevance
“…In this regard, Geijer et al [29] reported the course of a lesion the healing of which took over 2.5 years. By contrast, clinical symptoms often improved signi cantly after 2 to 6 weeks [13,21,22,25,29,30,33]. A complete disappearance of symptoms was described at the earliest after 2 to 3 months of continuous therapy [7,13,17].…”
Section: Therapy Outcomesmentioning
confidence: 97%
See 3 more Smart Citations
“…In this regard, Geijer et al [29] reported the course of a lesion the healing of which took over 2.5 years. By contrast, clinical symptoms often improved signi cantly after 2 to 6 weeks [13,21,22,25,29,30,33]. A complete disappearance of symptoms was described at the earliest after 2 to 3 months of continuous therapy [7,13,17].…”
Section: Therapy Outcomesmentioning
confidence: 97%
“…Two case reports radiologically demonstrated the primary overlay of fracture lines by BME [28,29]. Some studies failed to report the MRI criteria used for diagnosis [30][31][32][33]. In total, BME were observed in 92.9% of patients, whereas fractures were reported to be present in 44.7%.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…12,65 Iako većina pro vedenih istraživanja upućuje na povoljne učinke bis fosfonata, bitno je istaknuti da su ona provedena na malom uzorku bolesnika te da su upotrijebljeni i drugi lijekovi poput nesteroidnih protuupalnih lijekova, vitamina D i kalcija (tablica 3.). 5,12,[63][64][65][66][67] Kod primjene bisfosfonata potrebno je pratiti parametre bubrežne funkcije, jer brza intravenska primjena visokih doza može biti nefrotoksična. Kod peroralne primjene najčešće su zabilježene gastrointestinalne nuspojave poput iritacije ili erozije sluznice jednjaka, dok i kod peroralne i intravenske primjene može doći do reak cije akutne faze preosjetljivosti koja je prolazna i mani festira se simptomima sličnima gripi.…”
Section: Konzervativno Liječenjeunclassified